„Spowiedź żarliwego kinomana”, czyli inspiracje, budowa i styl plakatów filmowych Andrzeja Klimowskiego - Chojnacka, Justyna (Załącznik Kulturoznawczy, 2024)
In 1972, Andrzej Klimowski quit his painting and sculpture studies at St. Martin School of Art in London and moved to Warsaw to study at Henryk Tomaszewski’s poster studio at the Academy of Fine Arts in Warsaw. Franz Kafka, Albert Camus, Jean Paula Sartre, Jean Luc Godard, Andrzej Munk are only some of his literary and movie fascinations. His works are soaked with the style of the silent cinema, film noir or paintings of René Magritte. Being under the strong influence of i. a. Jan Lenica and Roman Cieślewicz, he designs posters brimming with references to the history of art. Over time, he has created his own individual, signature style and Taxi Driver, Dead Man or The Godfather are only a part of his impressive portfolio. Klimowski explains that it is better for the final effect, if the content of works is more expanded and full of iconographic elements. The article presents and analyzes the works by Andrzej Klimowski, taking into account his inspiration, composition structure and execution of the design of movie posters.